The last folk hero : [large type] the life and myth of Bo Jackson - Pearlman, Jeff (Harper Large Print, an imprint of HarperCollins Publishers, 2022)
Drawing on 720 original interviews, a New York Times best-selling sportswriter captures as never before the elusive truth about the greatest athlete of all time who took the world by storm from the mid-1980s into the early 1990s--and then, almost overnight, disappeared.